From drought to displacement: Assessing the impacts of climate change on conflict and forced migration in West Africa's Sahel Region - Ejemai Eboreime; Omolayo Anjorin; Chisom Obi-Jeff; Tunde M. Ojo; Attila Hertelendy (The Journal of Climate Change and Health)
Across Africa's semiarid Sahel region, temperatures have risen faster than the global average, resulting in severe threats to water access, food security, and human health. Key climate factors such as desertification interact with ethnic and economic tensions, exacerbating violence between pastoral and farming groups competing over degraded productive land and water resources. Mounting climate pressures act as threat multipliers for both violent conflict and internal displacement across countries spanning Senegal to Sudan. This perspective examines intersections of climate change, violent clashes, and forced migration using incidents in Nigeria and Burkina Faso—where droughts, floods and agricultural losses continue to worsen. With 8 million internally displaced persons in the region now, urban areas face overburdened infrastructure while attempting to host influxes of traumatized, impoverished migrants facing further risks. This article argues that integrated policy action is urgently needed to mitigate climate change, enhance community resilience, and protect vulnerable groups to ease cascading humanitarian crises and achieve development goals amid spiraling environmental pressures across West Africa.